2021
DOI: 10.21101/cejph.a6672
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severe pneumonia: Prospective multicentre study on demands on intensive care capacities

Abstract: Objectives: The aim of the study was to obtain data on demands on the intensive care capacities to treat COVID-19 patients, and to identify predictors for in-hospital mortality.Methods: The prospective observational multicentre study carried out from 1 March till 30 June 2020 included adult patients with confirmed SARS-CoV-2 infection with respiratory failure requiring ventilatory support or high-flow nasal oxygen therapy (HFNO).Results: Seventy-four patients, 46 males and 28 females, median age 67.5 (Q1-Q3: 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Characteristics of patients and included studies are shown in Table S3 . Patients were hospitalized in a hospital ward [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] or ICU [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and studies were conducted in different countries (Andorra [ 38 ], Belgium [ 29 ], Brazil [ 14 ], China [ 15 , 16 ], Czech Republic [ 28 ], Denmark [ 17 ], France [ 18 , 19 , 20 , 29 ], India [ 30 ], Italy [ 31 ], Mexico [ 22 , 23 , 32 ], Norway [ 24 ], Poland [ 25 ], Spain [ 26 , 33 , 34 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of patients and included studies are shown in Table S3 . Patients were hospitalized in a hospital ward [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] or ICU [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and studies were conducted in different countries (Andorra [ 38 ], Belgium [ 29 ], Brazil [ 14 ], China [ 15 , 16 ], Czech Republic [ 28 ], Denmark [ 17 ], France [ 18 , 19 , 20 , 29 ], India [ 30 ], Italy [ 31 ], Mexico [ 22 , 23 , 32 ], Norway [ 24 ], Poland [ 25 ], Spain [ 26 , 33 , 34 ,…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviations: USA = United States of America; UK = United Kingdom; IC = confidence interval. References: Brandão et al [ 14 ]; Cao et al [ 15 ]; Yang et al [ 16 ]; Madsen et al [ 17 ]; Jourdes et al [ 18 ]; Kaeuffer et al [ 19 ]; Allenbach et al [ 20 ]; Giacomelli et al [ 21 ]; Cortes-Telles et al [ 22 ]; Olivas-Martínez et al [ 23 ]; Myrstad et al [ 24 ]; Piwowarczyk et al [ 25 ]; Rodriguez-Molinero et al [ 26 ]; Roberts et al [ 27 ]; Dzupová et al [ 28 ]; Schmidth et al [ 29 ]; Kayina et al [ 30 ]; Radovanovic et al [ 31 ]; Namedys-Silva et al [ 32 ]; Estella et al [ 33 ]; Barrasa et al [ 34 ]; Rodríguez et al [ 35 ]; Pineiro et al [ 36 ]; Taboada et al [ 37 ]; Ferrando et al [ 38 ]; Larsson et al [ 39 ]; Thomson et al [ 40 ]; Gupta et al [ 41 ]; Molnar et al [ 42 ]; Cummings et al [ 43 ].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the studied variable (time between HFNC initiation and IMV initiation), the study included ten events of mortality for each confounding variable assessed, for a total of 12 confounders. Assuming an expected mortality of 40% [ 29 ], the required sample size was 325 patients.…”
Section: Methodsmentioning
confidence: 99%